2010
DOI: 10.1016/j.virol.2010.04.030
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of naturally occurring influenza H3NA− viruses lacking the NA gene segment: Toward a new mechanism of viral resistance?

Abstract: Among a panel of 788 clinical influenza H3N2 isolates, two isolates were characterized by an oseltamivir-resistant phenotype linked to the absence of any detectable NA activity. Here, we established that the two H3NA- isolates lack any detectable full-length NA segment, and one of these could be rescued by reverse genetics in the absence of any NA segment sequence. We found that the absence of NA segment induced a moderate growth defect of the H3NA- viruses as on cultured cells. The glycoproteins density at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…However, in the latter case and in contrast to our variants with NA deletions, attempts to isolate a neuraminidase-negative virus strain were not successful, and the authors therefore suggested that full-length segment 6 remained in the virus population at a lower frequency. A complete loss of a neuraminidaseencoding segment or neuraminidase function is deemed impossible (41), with the only example of this being in a human H3 isolate which was claimed to lack the complete segment 6 and addressed as a seven-segmented influenza A virus (42). Alternatively, the growth of a neuraminidase-negative influenza A virus without supplementation of exogenous sialidase was demonstrated in vitro and in mice only if the loss of neuraminidase activity was accompanied by mutations around the HA receptor-binding pocket, which lowered the avidity for receptors (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the latter case and in contrast to our variants with NA deletions, attempts to isolate a neuraminidase-negative virus strain were not successful, and the authors therefore suggested that full-length segment 6 remained in the virus population at a lower frequency. A complete loss of a neuraminidaseencoding segment or neuraminidase function is deemed impossible (41), with the only example of this being in a human H3 isolate which was claimed to lack the complete segment 6 and addressed as a seven-segmented influenza A virus (42). Alternatively, the growth of a neuraminidase-negative influenza A virus without supplementation of exogenous sialidase was demonstrated in vitro and in mice only if the loss of neuraminidase activity was accompanied by mutations around the HA receptor-binding pocket, which lowered the avidity for receptors (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…To do so, viral RNA was extracted from the infected MDCK cell-culture supernatant by using the QIAamp viral RNA minikit (Qiagen) according to the manufacturer's instructions. A twostep RT-PCR was carried out for full-length amplification of each viral RNA gene segment, by using the influenza A universal RT primer 5′-AGC AAA AGC AGG-3′ (Eurogentec) (46). The cDNAs obtained from the different genes were cloned into the pHW2000 vector (47) allowing expression of both negative-and positive-strand RNAs and viral proteins from two different promoters.…”
Section: Methodsmentioning
confidence: 99%
“…We used an eight-plasmid system to generate viruses in the A/Moscow/10/99 H3N2 background (28). cDNAs were cloned in the pHW2000 plasmid as already described (42). Mutations were introduced in the NA plasmid using the QuikChange site-directed mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…Infectious titers (doses infecting 50% of the cell culture [TCID 50 ]/50 l) were performed in confluent MDCK and MDCK-SIAT1 cells as previously described (42). The cytopathic effect was visible after incubation at 34°C for 96 h, and the test was revealed by hemagglutination tests performed with 0.5% chicken red blood.…”
Section: Methodsmentioning
confidence: 99%